'This neo-natal ménage à trois': British media framing of transnational surrogacy. (1st January 2016) - van den Akker, O.; Fronek, P.; Blyth, E.; Frith, L.
Abstract: Background: Media framing can influence people's perceptions of social changes in family building, and has the potential to influence their future actions.Objectives: to analyse the type of framing and construction used in British newsprint of transnational commercial surrogacy.Methods: UK newspapers were searched using the search engine Lexis-Nexis. One hundred and ninety-seven articles were analysed. Content analysis was undertaken to identify the use of gain, loss, neutral, alarm and vulnerability frames, as well as type of construction (i.e. ethical, social, legal, financial and medical). Four researchers independently analysed articles using a coding strategy.Results: Differences between serious (mainly legal, financial), middle-market (legal) and tabloid (social, financial) newspapers were found. There were three main foci; buying babies – affordable only to those wealthy enough to pay for it; the legal complications of transnational surrogacy – reporting a sense of the legal system lagging behind this practice; and gay families – repeatedly questioning their suitability as parents – demonstrating a prevailing heterosexual stereotype about reproduction and parenting.Conclusions: Stereotyping was prevalent and the welfare of children and medical aspects of transnational surrogacy were minimally addressed, indicating the media selectively influences its readership.